Economic Literacy Model for Teens: Does the Book based on e-book Picture Stories as a Strategy to Avoid Impulsive Purchase Decision? - UTAMI, SE, MSi, Nunung Nurastuti (Journal of Research in Educational Sciences; Vol 9 No 11 (2018): JRES Volume IX Number 11_2018DO - 10.14505//jres.v9.11.03, 2019)
Globalization has a significant impact on the Indonesian economy as globalization opens opportunities for global products to the domestic market, with an indication of the number of malls that show a high consumptive culture among the public, the phenomenon of psycho economic impulse buying related to money and lifestyle, especially for teenagers ages 10 years to 24 years. This study aims to prepare teens in the face of globalization that strengthens their character by teaching economic literacy through the development and implementation of economic literacy book based e-book Picture Stories for easy to understand and fun to read. In the first step of research is conducted to get a portrait of economic literacy implementation on teens and to explore what they need for materials to create prototype predesign book economic literacy based e-book Picture Stories. The result of data analysis obtained information that teens Malang city Indonesia knows literacy less, medium to very low by 81,3%., and only 18,7% high ability. Furthermore, it found that economic literacy and self-control have a negatives significant effect on the impulsive behaviour of -0,274 and -0,669, low percentage of knowledge about micro and macroeconomic literacy based on the indicator of The Standard in Economic Survey developed by NCEE. Based on the information, it is necessary to increase the understanding of economic literacy namely the availability of a book that is fun to read "Now's Era" teenagers. it is a reading book following the penchant teens of economic literacy book based on e-book Picture Stories that, so they will be comfortable and happy to read through notebooks, gadget, hand phone android and so on